Liquid thin film dewetting-driven micropatterning of reduced graphene oxide electrodes for high performance OFETs. Issue 1 (10th December 2018) - Lee, Sung Min; Song, Seung Keun; Yoon, Seongwon; Chung, Dae Sung; Chang, Suk Tai
Abstract : High resolution micropatterning of rGO electrodes based on the dewetting of liquid thin films is presented. Abstract : We present a novel approach to produce high-resolution reduced graphene oxide (rGO) micropatterns based on a dewetting phenomenon of liquid thin films. The uniform liquid thin film of aqueous graphene oxide (GO) dispersion was formed by the meniscus dragging deposition method on a pre-patterned silanized substrate. Subsequently, selective dewetting of the water layer was induced due to the surface energy gradient on the coating substrates. After drying and chemical reduction, the high-resolution rGO micropatterns with a minimum feature size of 10 μm were realized over a large area substrate by consuming less than 1 μL of GO solution per square centimeter. As a demonstration of the application of this patterning technique, we have successfully fabricated organic field-effect transistors (OFETs) based on rGO pattern arrays as source–drain electrodes. The OFETs with the rGO electrodes exhibited a field effect mobility of 0.6 cm 2 (V s) −1 with an on/off ratio of 1.79 × 10 6, which is higher than that of the devices with Au source–drain contacts.